2008
DOI: 10.1038/onc.2008.66
|View full text |Cite
|
Sign up to set email alerts
|

Threonine 74 of MOB1 is a putative key phosphorylation site by MST2 to form the scaffold to activate nuclear Dbf2-related kinase 1

Abstract: Mammalian nuclear Dbf2-related (NDR) kinases (LATS1 and 2, NDR1 and 2) play a role in cell proliferation, apoptosis and morphological changes. These kinases are regulated by mammalian sterile 20-like kinases (MSTs) and Mps one binder (MOB) 1. Okadaic acid (OA), which activates MST2, facilitates the complex formation of MOB1, MST2 and NDR1 in HEK293FT cells. The in vitro biochemical study demonstrates the phosphorylation of MOB1 by MST2. The phosphorylated MOB1 alone is capable to partially activate NDR1 in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 24 publications
(29 reference statements)
0
55
0
Order By: Relevance
“…No differences in phospho-MST1, total MST1, or total SAV1 were detected. We then stimulated imMob1DKOLP ± Tmx cells with okadaic acid (OA), which activates MST1/2 (40), and performed immunoblotting after adjusting lysates to equality of LATS1 protein. Whereas OA-stimulated imMob1DKOLP-Tmx cells showed vigorous LATS1 phosphorylation, OA-stimulated imMob1DKOLP+Tmx cells did not (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…No differences in phospho-MST1, total MST1, or total SAV1 were detected. We then stimulated imMob1DKOLP ± Tmx cells with okadaic acid (OA), which activates MST1/2 (40), and performed immunoblotting after adjusting lysates to equality of LATS1 protein. Whereas OA-stimulated imMob1DKOLP-Tmx cells showed vigorous LATS1 phosphorylation, OA-stimulated imMob1DKOLP+Tmx cells did not (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of Mst1/2 leads to phosphorylation and activation of their direct substrates, Lats1/2 (Chan et al, 2005). Mob1, which forms a complex with Lats1/2 (Chow et al, 2010), is also phosphorylated and activated by Mst1/2, resulting in enhanced interaction between Lats1/2 and Mob1 (Hirabayashi et al, 2008;Praskova et al, 2008). Similar to that in Drosophila, MST1/2/Sav1 and Lats1/2/Mob1 form a physical and functional core of the Hippo pathway.…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 95%
“…2B, compare with Fig. 2A), including: phosphorylation of Lats (Wts), Mob (Mats) and WW45 (Sav) proteins by Mst (Hpo) kinases (Callus et al, 2006;Chan et al, 2005;Hirabayashi et al, 2008;Praskova et al, 2008); the association of WW45 with Mst and Lats (Callus et al, 2006;Lee et al, 2008); a requirement for WW45 for the phosphorylation of Lats (Lee et al, 2008); the association of Mob and Lats and the consequent promotion of Lats autophosphorylation (Praskova et al, 2008); and the phosphorylation of the Yki homologue Yes-associated protein (Yap) by Lats (Dong et al, 2007;Hao et al, 2008;Zhang et al, 2008a;Zhao et al, 2007). Studies of Mst in mammalian cells have identified autophosphorylation as being a crucial regulatory step for Hpo/Mst (Glantschnig et al, 2002;Lee and Yonehara, 2002), and have identified an association of Mst with Ras association domain family proteins (Praskova et al, 2004), which was subsequently also observed in Drosophila (Polesello et al, 2006).…”
Section: The Hippo Kinase Cassette In Drosophilamentioning
confidence: 99%